Influence of Heat on Protein Degradation, Histology and Eating Quality Indicators of Chicken Meat - Muthulakshmi, M.; Chandirasekaran, V.; Kalaikannan, A.; Jagadeeswaran, A.; Selvaraju, G.; Muthukumar, M.; Krupakaran, R. Prakash; Vasanthi, C.; Irshad, A. (International Journal of Bio-resource and Stress Management, 2022)
The experiments were carried out during February–July, 2021 at the Department of Livestock Products Technology (Meat science), Veterinary College and Research Institute, Namakkal, Tamil Nadu Veterinary and Animal Sciences University, India to assess the influence of heat on protein degradation, histology and eating quality indicators of chicken. Meat samples were taken from the broiler breast and cooked for the targeted end point temperature (75°C, 83°C, 89°C and 94°C) then assessed pH, colour, cooking loss, shear force value, protein degradation (SDS PAGE) and structure of muscle fibers. The heating temperature had a significant effect on pH and shear force value (p<0.01) at 94°C. Colour L* decreased significantly (p<0.01) and a* and b* value increased significantly (p<0.01) of cooked chicken breast at increasing end point cooking temperature. Progressive increasing (p<0.01) trends of cooking loss were noticed during the rising of end point cooking temperature. There were no significant differences between muscle fiber diameters. But significant (p<0.01) differences were observed in the sarcomere length of cooked chicken meat, showing decreasing trends during increasing temperature. Analysis of SDS-PAGE showed that the intensity of the myofibrillar protein band gradually decreased during chicken meat cooking at a higher endpoint temperature and inferring that the meat protein had changed. The heating temperature had a significant effect on sensory quality of cooked chicken breast at increasing end point cooking temperature. This study revealed that meat cooking at high-end point temperatures affects the meat quality by degradation of muscle proteins and changes in muscle structure.